2016
DOI: 10.1007/s13594-016-0299-9
|View full text |Cite
|
Sign up to set email alerts
|

Hot brining of pasta filata cheese: effect of sodium and calcium chloride on composition, yield, and hardness

Abstract: The aim of this study was to investigate how the yield and waterholding capacity of pasta filata cheese during scalding-kneading (approx. 60°C) can be improved by sodium chloride content in the stretching water. This is of sensorial and economic interests. The mechanism of hot bringing was further elucidated by adding calcium chloride in the stretchwater. Pasta filata cheese, comparable with high-moisture mozzarella, was produced in a benchtop batch scalding-kneader, with stretchwater containing 1.0, 2.0 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Different effects were observed in different types of mozzarella pasta filata cheeses. In high moisture mozzarella cheeses, an increase in sodium content increased the protein water-holding capacity so that the dry matter content is reduced, leading to decreased hardness (Bahler, Kunz, & Hinrichs, 2016). In contrast, in another type of mozzarella cheese, a lower addition of salt in the curd decreased hardness, of both full-fat and reduced-fat cheeses (Henneberry, Wilkinson, Kilcawley, Kelly, & Guinee, 2015), this effect being modulated by the calcium content.…”
Section: Impact Of Cheese Composition On Texturementioning
confidence: 99%
“…Different effects were observed in different types of mozzarella pasta filata cheeses. In high moisture mozzarella cheeses, an increase in sodium content increased the protein water-holding capacity so that the dry matter content is reduced, leading to decreased hardness (Bahler, Kunz, & Hinrichs, 2016). In contrast, in another type of mozzarella cheese, a lower addition of salt in the curd decreased hardness, of both full-fat and reduced-fat cheeses (Henneberry, Wilkinson, Kilcawley, Kelly, & Guinee, 2015), this effect being modulated by the calcium content.…”
Section: Impact Of Cheese Composition On Texturementioning
confidence: 99%
“…Impact of the thermo-mechanical threatments and hot brining on composition, yield, solid loss, microstructure and hardness of pasta filata cheese were proved (Bähler, 2016;Banville, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Since cheese is a soft gel of concentrated casein micelles with embedded fat globules and a continuous serum phase, the swelling of this concentrated protein network increases in the presence of sodium chloride. In particular, the voluminosity (size) of the casein micelles increases (Bähler et al, 2016). Also Everett and Auty (2008) reported that salt limits the action of bacteria in cheese, as well as has secondary effect of flavor enhancement.…”
Section: Article Infomentioning
confidence: 99%